Efficient estimation with a priori information - Rothenberg, Thomas J. (New Haven, Yale University Press, 1973)
Over the years econometricians have developed special statistical methods for handling the problems that arise in analyzing economic data.
Includes Bibliographical references, index
II 16/01/2019
Loans
Keywords: Econometrics; Estimation theory